Response of Nitrogen and Sulfur on the Oil Content of Sesame and Nutrient Status of Soil - Shilpi, Sonia; Nuruzzaman, Md.; Akhter, Fahmina; Islam, M. N.; Sutradher, G. N. C. (International Journal of Bio-resource and Stress Management, 2014)
A study was conducted to see the influence of different levels of nitrogen and sulphur on oil content of sesame and nutrient status of soil during 2009 at the field of Sher-e-Bangla Agricultural University farm, Sher-e-Bangla Nagar, Dhaka, Bangladesh. The experiment consisted of two factors. 4 levels of nitrogen N0: 0 kg N/ha (control); N1: 40 kg N ha-1; N2: 60 kg N ha-1 and N3: 100 kg N ha-1; and 4 levels of sulfur S0: 0 kg S ha-1 (control); S1: 20 kg S ha-1; S2: 40 kg S ha-1 and S3: 60 kg S ha-1. Oil content increased significantly with increasing N level upto 60 kg N ha-1 (N2) whereas the concentration of N, P, K and S in plant increased upto 100 kg N ha-1. On the other hand, oil content increased significantly with increasing S level upto 40 kg S ha-1 (S2) whereas N, P, K and S concentration in plant increased upto 60 kg S ha-1. The maximum oil content of sesame (46.98%) was recorded from the combined application of 60 kg N ha-1 and 60 kg S ha-1.